Accelerating the Globalization of America : the Role of Information Technology. - Mann, Catherine L. (Peterson Institute for International Economics, 2006)
"Information technology (IT) is the most robust sector in the global economy, outpacing investment and trade growth for any other product and also pushing for more globalization of many other industries. Globalization of US IT firms has promoted deeper integration of IT throughout the US economy, which in turn has promoted more extensive globalization in other sectors of the US economy and labor market. Catherine Mann traces the globalization of the industry, its diffusion into the US economy, and the implications of more extensive technology-enabled globalization of products and services."--Jacket.